Psathyrella alpina sp. nov. (Psathyrellaceae, Agaricales), a new species from China - Yan, Jun-Qing; Bau, Tolgor (Phytotaxa, 2018)
Psathyrella alpina sp. nov. is described as a new species from Yunnan and Jiangxi Province, China. This species is distinctive due to its median-size basidiospores, fusiform to lageniform pleurocystidia and special pileipellis which consists of vesiculose cells, covered by a 1 cells deep layer of hyphae. It is also unique compared to related Psathyrella species in phylogenetic analysis of ITS sequences. Detailed illustrations, field photographs and microscopic features of basidiomata are provided in this paper.